Using public health law to contain the spread of COVID-19. (12th March 2020) - Griffith, Richard
Abstract : Richard Griffith, Senior Lecturer in Health Law at Swansea University, considers what powers are available to ministers, health and local authorities to minimise the spread of the novel coronavirus and the disease it causes